THE EFFECTIVENESS OF TAX OPTIONS IN THE DIVISION OF TAXATION REVENUE: Perspectives on Fiscal Equity and Decentralisation - Rustian Mushawirya; Firdaus Arifin; Ihsanul Maarif; Robi Assadul Bahri; Anastasia Wahyu Murbani (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
Fiscal decentralisation in Indonesia aims to strengthen regional autonomy and promote fiscal equity through instruments such as tax surcharges. However, there are significant disparities in the utilisation of tax surcharges between advanced and underdeveloped regions, raising concerns about the effectiveness of this instrument in reducing fiscal inequality. This study seeks to evaluate the effectiveness of tax surcharges in supporting equitable fiscal redistribution in Indonesia, with a focus on regional differences in fiscal capacity. The research employs a normative-empirical method involving policy analysis and empirical data from regions implementing tax surcharges. The findings reveal that regions with greater fiscal capacity can better leverage tax surcharges, while underdeveloped regions remain reliant on fiscal transfers from the central Government. Administrative constraints and limited technical capacity in underdeveloped regions are significant obstacles. The implications of these findings highlight the need for enhanced administrative and fiscal capacity in disadvantaged regions, more flexible tax policy reforms, and further studies to assess the long-term impact of tax surcharges in promoting fiscal equity.